1959
DOI: 10.1126/science.130.3376.624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light on Motility, Life-Span, and Respiration of Bovine Spermatozoa

Abstract: Exposure to light of bovine spermatozoa suspended in various media results in a progressive decline in metabolic activity followed by the premature death of the cells. The inhibitory and spermicidal effects of visible light resemble a photodynamic action; the photosensitizer is an intrinsic component of the cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1961
1961
1970
1970

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…This effect is probably the result of a direct change within the spermatozoon itself brought about by the ultraviolet irradiation. Goldberg (1959, 1961) found that white light caused intracellular damage to spermatozoa and that catalase protected against this damage. In the present studies, catalase afforded similar protection against ultraviolet irradiation of spermatozoa.…”
Section: (E) Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is probably the result of a direct change within the spermatozoon itself brought about by the ultraviolet irradiation. Goldberg (1959, 1961) found that white light caused intracellular damage to spermatozoa and that catalase protected against this damage. In the present studies, catalase afforded similar protection against ultraviolet irradiation of spermatozoa.…”
Section: (E) Statistical Analysismentioning
confidence: 99%
“…Thus Hamner and Williams (1961) found that incident light increases the rate of oxygen uptake by bull spermatozoa. On the other hand, longer exposure to white light or to wavelengths of 430 and 550 ill", has a deleterious effect on the motility and respiration of bovine spermatozoa (Norman and Goldberg 1959;. This effect is thought to be due to activation of a photosensitive agent within the spermatozoa having a maximum absorption in the blue portion of the visible spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Among the prokaryotes visible radiation and near-ultraviolet radiation have been reported to kill or inhibit the growth of the heterotropic bacteria Streptococcus salivarius (4), Escherichia coli (17,19,20) (8,31), the colorless algae Prototheca zopfii (14) and Astasia longa (8), and the yeast Saccharomyces cerevisiae (10,15,24,25,34), have also been reported to be inhibited by blue light. Various processes in cells of higher plants and animals have also been reported to be inhibited by blue or near-ultraviolet light, such as cell division (21, 42), respiration (35,33) and motility of sperm (41,28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Various processes in cells of higher plants and animals have also been reported to be inhibited by blue or near-ultraviolet light, such as cell division (21,42), respiration (35,33) and motility of sperm (41,28,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation